2001
DOI: 10.2460/javma.2001.218.1120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of dogs with grade-II mast cell tumors treated with surgery alone: 55 cases (1996–1999)

Abstract: Results suggest that additional local treatment may not be required after complete excision of grade-II mast cell tumors and that most dogs do not require systemic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
155
9
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(198 citation statements)
references
References 12 publications
14
155
9
20
Order By: Relevance
“…Some reports indicated that moderate differentiated mast cell tumors can have a favorable prognosis (if treated appropriately) as in the case of highly differentiated mast cell tumors (Seguin et al, 2001;Weisse et al, 2002;Murphy, 2003). The survival rate is around 3.5 years in about 55% of subjects (Ginn et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Some reports indicated that moderate differentiated mast cell tumors can have a favorable prognosis (if treated appropriately) as in the case of highly differentiated mast cell tumors (Seguin et al, 2001;Weisse et al, 2002;Murphy, 2003). The survival rate is around 3.5 years in about 55% of subjects (Ginn et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Os dados do presente estudo corroboram a literatura , Webster et al 2007), pois os tumores nessas localizações estão relaQuadro 4. Distribuição das duas classificações histológicas, marcadores imuno-histoquímicos e análise da PCR Forrest (1997), que relatou que os mastocitomas nos membros tinham comportamento benigno, e com Oliveira (2008), que classificou a maioria dos mastocitomas no membro como de grau I. Os tumores disseminados apresentavam graus baixos e padrão perimembranoso, o que corrobora com os autores (Thamm et al 1999, Séguin et al 2001, Thamm & Vail 2001 que não os associam a piores prognósticos.…”
Section: Discussionunclassified
“…Tumor recurrence developed in a small number of dogs with completely excised, grade II, cutaneous mast cell tumors [21,27], suggesting that a complete excision can reduce recurrence. In a prior study, the frequency of recurrence in complete surgical excision within 24 months postoperatively was significantly lower than in incomplete surgical excision [13].…”
Section: Discussionmentioning
confidence: 99%
“…In grade II tumors, a complete surgical margin accurately predicted a good prognosis [21,27]. The frequency of recurrence in the complete surgical excision cases was significantly lower than in incomplete surgical excision during 24 months following surgery [13].…”
mentioning
confidence: 92%
See 1 more Smart Citation